Pengaruh Pemberitaan Media terhadap Penyebaran Ujaran Kebencian & Implikasinya terhadap UU No. 40 Tahun 1999 - Pradipta Larasati Annisa Aulia Hapsari; Athiatus Salam; Syaira Ananda Crisnandi; Taun Taun (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The development of technology and freedom of the press in the digital era has brought great changes in the form and manner of news delivery by the mass media. However, in reality, the media often becomes a means of spreading hate speech that has a negative impact on society and the democratic order. This article aims to examine how media coverage can contribute to the dissemination of hate speech and its impact on the application of Law No. 40/1999 on the Press. Through a qualitative research method approach with a descriptive and inductive approach, this article evaluates the media's responsibility to deliver information objectively and identifies elements in the news that can accelerate the spread of hate speech, such as provocative elements, lack of verification, and excessive news presentation. In this context, the active role of supervisory institutions such as the Press Council is needed so that press freedom continues to run in line with journalistic ethics and applicable laws, in order to maintain social cohesion and uphold democratic values in Indonesia.